Angiogenesis as a therapeutic target in arthritis in 2011: learning the lessons of the colorectal cancer experience. - Thairu, N; Kiriakidis, S; Dawson, P; Paleolog, E (Springer Verlag, 2011)
The paradigm of a therapy aimed at inhibiting the formation of blood vessels, which would consequentially deprive cells and tissues of oxygen and nutrients, was born from the concept pioneered by the late Judah Folkman that blood vessel formation is central to the progression and maintenance of diseases which involve cellular metabolism and tissue expansion, and cancer in particular. The prototype targeted angiogenesis inhibitor anti-vascular endothelial growth factor (VEGF) antibody bevacizumab was approved in 2004 for colorectal cancer, and has since been approved for other cancers. Rheumatoid arthritis (RA) is a chronic inflammatory disease, during which inflamed tissue invades and destroys cartilage and bone. The tissue expansion, invasion, expression of cytokines and growth factors and areas of hypoxia which are a feature of RA have resulted in the hypothesis that angiogenesis inhibition may also be beneficial in RA, drawing on the success of bevacizumab. This review focuses on our current understanding of the importance of angiogenesis in RA, and on the lessons which may be learnt from the clinical experiences of angiogenesis blockade, particularly in colorectal cancer.